Czech Pagans’ Views on Extremism - Merička, Jan; Smolik, Josef (Pomegranate, 2018)
The chief aim of this paper is to describe the relationship of contemporary Czech Pagans-those who identify themselves as such and practice their belief in ritual-to what is described as extremism, using the methods of qualitative analysis, interviews and observation. The paper focuses on the subjective views of Pagans themselves, which allow us to understand the internal processes within this highly particular community. An important element of this is how Pagans themselves understand the term "extremism." The paper outlines specific positions taken by individual Pagans, proceeding to generalize in order to characterize the Czech Pagan community as a whole. It also analyses potential trigger mechanisms, which in some cases entice individuals from the community to take extremist positions.